Juridical Review Of Fine Art Works Created Using Artificial Intelligence Technology Art Generator - D. Matona, Marshanda Adella; Almoravid Dungga, Weny; Fazri Elfikri, Nurul (Estudiante Law Journal, 2025)
This study examines legal challenges surrounding AI-generated artworks, focusing on copyright protection in Indonesia. AI art raises concerns about authenticity and ownership, prompting an analysis of existing copyright laws through a normative juridical approach and literature review. Findings show that many AI-created works fail to meet originality criteria under current laws, exposing regulatory gaps. The study also addresses issues with using copyrighted works as AI training data, particularly regarding royalties and protection on social media. Results highlight insufficient policies for creators and developers, emphasizing the urgent need for clearer legal frameworks to safeguard rights and support fair AI use in creative fields.